2021
DOI: 10.1038/s41536-021-00139-x
|View full text |Cite
|
Sign up to set email alerts
|

Notch-Wnt signal crosstalk regulates proliferation and differentiation of osteoprogenitor cells during intramembranous bone healing

Abstract: Adult bone regeneration is orchestrated by the precise actions of osteoprogenitor cells (OPCs). However, the mechanisms by which OPC proliferation and differentiation are linked and thereby regulated are yet to be defined. Here, we present evidence that during intramembranous bone formation OPC proliferation is controlled by Notch signaling, while differentiation is initiated by activation of canonical Wnt signaling. The temporospatial separation of Notch and Wnt signal activation during the early stages of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…The main molecular regulators of the bone healing cascade are bone morphogenetic proteins (BMPs), the fibroblast growth factor (FGF), transforming growth factor-β1, and vascular endothelial growth factor [3]. In addition, multiple signaling pathways regulate osteogenesis, including Wnt, Notch, parathyroid hormone (PTH), and hedgehog (Hh) [48,49].…”
Section: Cytokines Growth Factors and Signaling Pathways Enhancing Osteogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The main molecular regulators of the bone healing cascade are bone morphogenetic proteins (BMPs), the fibroblast growth factor (FGF), transforming growth factor-β1, and vascular endothelial growth factor [3]. In addition, multiple signaling pathways regulate osteogenesis, including Wnt, Notch, parathyroid hormone (PTH), and hedgehog (Hh) [48,49].…”
Section: Cytokines Growth Factors and Signaling Pathways Enhancing Osteogenesismentioning
confidence: 99%
“…Interestingly, Lee et al suggest that there is a crosstalk between the Notch and Wnt signaling pathways. Their study demonstrated that the regulation of osteoprogenitor cell proliferation during the formation of intramembranous bone was controlled by the Notch pathway, whereas the canonical Wnt pathway initiated the differentiation of osteoprogenitor cells [49].…”
Section: Cytokines Growth Factors and Signaling Pathways Enhancing Osteogenesismentioning
confidence: 99%
“…Canonical Wnt promoted MSC differentiation towards the osteoblast lineage; however, Hes1-induced Notch activation attenuated this effect of canonical Wnt, thereby inhibiting MSC osteogenic differentiation 40 , 43 . Crosstalk between Notch and canonical Wnt was observed during the early stages of intramembranous bone regeneration 44 . Notch regulated osteoprogenitor cell proliferation, and this effect was terminated by canonical Wnt activation, leading to osteogenic differentiation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between Notch and canonical Wnt was observed during the early stages of intramembranous bone regeneration 44 . Notch regulated osteoprogenitor cell proliferation, and this effect was terminated by canonical Wnt activation, leading to osteogenic differentiation 44 . Similarly, the NICD was reported to occupy and inhibit T-cell factor/lymphoid enhancer factor at its binding functional domain, suggesting the underlying mechanism by which Notch exerts an inhibitory effect on the canonical Wnt signaling pathway 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, the Wnt pathway can be stimulated or inhibited by other signalling pathways and vice versa; Wnt signalling activity can transactivate other signalling pathways [ 129 ]. In bone cells, Wnt was shown to interact with Bone morphogenic protein (BMP) signalling [ 130 , 131 ], the RANK/RANKL/NF-κB pathway, Hippo, Notch [ 132 ] and Hedgehog [ 133 , 134 ] signalling pathways, mTOR and epidermal growth factor (EGF) signalling [ 135 ] and most probably several others that have not been explored yet. Most of these interactions have been confirmed on the level of canonical Wnt signalling.…”
Section: Non-canonical Wnt Crosstalk With Other Signalling Pathwaysmentioning
confidence: 99%